The Case of the Dream Maker: Perec, Pontalis, and Dream Writing - Aubrey Gabel (Studies in 20th & 21st Century Literature, 2021)
This article considers Georges Perec’s La Boutique obscure as a literary experiment in dream writing, by putting it in dialogue with French Freudianism, notably the clinical papers of J.-B. Pontalis, Perec’s long-time psychoanalyst. Pontalis describes a patient type, the "dream maker,” who provokes an extreme case of counter-transference and requires new methods in dream therapy. Pontalis, like many of Perec’s literary critics, was suspicious of the authenticity of Perec's dream journal and denied it both therapeutic and literary status. This article reinserts La Boutique obscure into Perec’s literary program. Through a discussion of the text's formal attributes and its sociological context of production, the article demonstrates that Perec drew on non-psychoanalytic traditions of dreams, like dream journals and dream sociology, and continuously undercut any symbolic readings of his text. Most importantly, the article investigates the journal’s most fraught endeavor: experiencing and writing the concentration camp in dreams. Lucid dreaming becomes a ludic space for experiencing the unexperiencable horrors of history.
Keywords: Georges Perec; J.-B. Pontalis; ludics; dreams; psychoanalysis; sociology